Comparison between organic solar cells and perovskite photovoltaic cells: Minireview - Min, Soon; Chowdhury, Md. Hojaifa Daiyan; Chowdhury, Muhammad Rashique Hamjah; Chowdhury, Md. Iqbal Bahar (International Journal of Innovative Research and Scientific Studies, 2025)
The photophysics, working principles of organic and perovskite solar cells, the main two photovoltaic technologies that received more attention from the scientific community in recent years are analyzed. For this, the current review focuses on connecting the intrinsic structural (such as crystalline, ionicity) as well as electronic (relative permittivity, binding energy) and optical (absorption coefficient) properties of these organic/perovskite photoactive layers to unveil deep understanding into charging carrier dynamics and recombination kinetics while establishing their relationship with film in tandem with device performance metrics. The review offers insight into the limitations related to both types of solar technologies that are hindering their performance & proposed succinct chart of remedies to cope up with them appropriately causing this bottleneck.